The importance of homocysteine levels in the prognosis of patients with chronic renal disease and in hemodialysis patients - Bruna M. Martella; Glaucia Raquel L. Veiga; Beatriz C. A. Alves; Ligia A. Azzalis; Virginia B. C. Junqueira; Flavia S. Gehrkei; Fernando Luiz A. Fonseca; Marcelo R. Bacci (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Introduction: Homocysteine (Hcy) is one of the metabolites of methionine (Met), an essential diet-derived amino acid. There is a close relationship between high plasma Hcy levels and declining renal function. Plasma and urinary Hcy level has been the target of studies as a biomarker that forecasts poor outcome in renal patients and in hemodialysis patients. This review evaluates the main studies that sought to correlate Hcy and poor prognosis in renal disease as well as the treatments proposed for the reduction of plasma Hcy levels in these patients. Conclusion: Hcy could be an important biomarker of renal disease progression mainly in hemodialysis patients. We emphasize the importance of normalizing plasma levels of this amino acid to ensure a better prognosis in kidney disease.